2022
DOI: 10.1136/bmjopen-2022-063538
|View full text |Cite
|
Sign up to set email alerts
|

Association between work stress and health behaviours in Korean and Japanese ageing studies: a cross-sectional study

Abstract: ObjectivesLimited research has focused on the association between work stress and health behaviours in Asian countries. We aimed to explore the effect of work stress on two health behaviours among employees aged 45 years or above in two countries with ageing populations, Korea and Japan.DesignA cross-sectional study.SettingThis secondary data analysis was conducted on baseline data from the Korean Longitudinal Study of Aging (KLoSA, 2006) and the Japanese Study of Aging and Retirement (JSTAR, 2007 and 2009).Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In European countries, individuals with a higher level of education may tend to understand and follow health-promoting methods, thereby attenuating the impact of environmental hazards [ 75 ]. In contrast, in other countries, particularly in Asia, although individuals with higher education might understand the hazards mentioned above, their ability to adopt healthy behaviors still may be limited by lifestyle [ 76 ] or occupational stress [ 77 ]. It has been verified that in China, individuals with a higher level of education are more inclined to prefer residential proximity to major roadways [ 32 ], which gives them access to richer social resources and shorter commute times.…”
Section: Discussionmentioning
confidence: 99%
“…In European countries, individuals with a higher level of education may tend to understand and follow health-promoting methods, thereby attenuating the impact of environmental hazards [ 75 ]. In contrast, in other countries, particularly in Asia, although individuals with higher education might understand the hazards mentioned above, their ability to adopt healthy behaviors still may be limited by lifestyle [ 76 ] or occupational stress [ 77 ]. It has been verified that in China, individuals with a higher level of education are more inclined to prefer residential proximity to major roadways [ 32 ], which gives them access to richer social resources and shorter commute times.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that working stress increased risk of dyslipidemia by affecting the HPA (Zhang et al., 2021 ), and chronic cortisol elevation increases glucocorticoid synthesis and glucose utilization, increases visceral fat deposition, and accelerates lipolysis, resulting in dyslipidemia (Kao et al., 2020 ). Additionally, working stress also affects smoking habits, a cross‐sectional study of the Asian population showed that working stress was significantly associated with smoking((OR = 1.45, 95%CI = 1.17–1.80) (Cheng et al., 2022 ). Shift work is the basic form of enterprise working time organization, which refers to the formation of work groups of different shifts within the working day, in the same work place for the production process.…”
Section: Discussionmentioning
confidence: 99%